Analisa Kualitas Pelayanan Publik Rumah Sakit Umum Daerah (RSUD) Kabupaten Sampang Menggunakan Indeks Kepuasan Masyarakat (IKM) - Assiddiq, Dafis Ubaidillah; Hamid, Abd. (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2023)
This study aims to determine public perceptions of public services in the form of health services provided by the Regional General Hospital (RSUD) in Sampang Regency using the Community Satisfaction Index (IKM). The research, which was conducted in 2023, used a survey method with 150 respondents from health service users at the Sampang District Hospital. From this study, it was found that health services at the Sampang District Hospital had an IKM conversion interval value of 72.15 or converted equivalent to the letter B. That is, the service level was in the good category.